Sclerostin antibody improves skeletal parameters in a Brtl/+ mouse model of osteogenesis imperfecta. (18th December 2012) - Sinder, Benjamin P; Eddy, Mary M; Ominsky, Michael S; Caird, Michelle S; Marini, Joan C; Kozloff, Kenneth M
Abstract Osteogenesis imperfecta (OI) is a genetic bone dysplasia characterized by osteopenia and easy susceptibility to fracture. Symptoms are most prominent during childhood. Although antiresorptive bisphosphonates have been widely used to treat pediatric OI, controlled trials show improved vertebral parameters but equivocal effects on long‐bone fracture rates. New treatments for OI are needed to increase bone mass throughout the skeleton. Sclerostin antibody (Scl‐Ab) therapy is potently anabolic in the skeleton by stimulating osteoblasts via the canonical wnt signaling pathway, and may be beneficial for treating OI. In this study, Scl‐Ab therapy was investigated in mice heterozygous for a typical OI‐causing Gly→Cys substitution in col1a1. Two weeks of Scl‐Ab successfully stimulated osteoblast bone formation in a knock‐in model for moderately severe OI (Brtl/+) and in WT mice, leading to improved bone mass and reduced long‐bone fragility. Image‐guided nanoindentation revealed no alteration in local tissue mineralization dynamics with Scl‐Ab. These results contrast with previous findings of antiresorptive efficacy in OI both in mechanism and potency of effects on fragility. In conclusion, short‐term Scl‐Ab was successfully anabolic in osteoblasts harboring a typical OI‐causing collagen mutation and represents a potential new therapy to improve bone mass and reduce fractures in pediatric OI. © 2013 American Society for Bone and Mineral Research